Effect of air annealing on the optical properties and luminescence performance of Ce:YAG ceramics for light-emitting diodes at different Ce concentrations. Issue 8 (July 2021) - Li, Xiaoyun; Chen, Jian; Liu, Zhuguang; Deng, Zhonghua; Huang, Qiufeng; Huang, Jiquan; Guo, Wang
Abstract: (Y1-x% Cex% )3 Al5 O12 (x = 0.2, 0.4, 0.6, 0.8, 1.0) transparent ceramics were fabricated by vacuum sintering technology, followed by air annealing at different temperatures. Transmittance of ceramics, valence of cerium, and luminescent properties with varying annealing temperatures are studied in detail. The negative effect of Ce 3+ oxidation induced by annealing gets increasingly evident when Ce concentration increases. Collaborating Ce:YAG ceramics with InGaN blue chips, light-emitting diodes (LEDs) with superior performance were constructed. The relationships between Ce concentration, annealing temperature, and luminous flux of LEDs are elucidated, showing that the optimized annealing temperature of Ce:YAG ceramics decreases from 1200 °C to 900 °C as Ce concentration increases from 0.2 at% to 1.0 at%. The luminous fluxes of optimized LEDs increase by ∼10 % compared with that of unannealed LEDs.